From Fragmentation to Integration: Educational Management Policy in Multidisciplinary Islamic Education - Muchammad Rozzaq Auwali; Titi Kadi (Journal of Educational Management Research, 2026)
This study aims to analyze the educational management policy of multidisciplinary Islamic education, particularly the integration of religious and general knowledge within the Islamic Education (PAI) curriculum. A qualitative approach was employed using descriptive analysis to explore how curriculum policies are designed and implemented in response to contemporary educational demands. The findings indicate that the curriculum, as a key instrument in achieving educational goals, is dynamic and continuously evolving to meet 21st-century competencies, including communication, collaboration, critical thinking, and digital literacy. The implementation of a multidisciplinary curriculum reflects a strategic policy effort to integrate religious and general sciences, positioning them as complementary rather than separate domains. This integration supports the development of holistic learners who are both intellectually competent and spiritually grounded. From an educational management perspective, the study highlights the importance of policy planning, curriculum organization, and implementation strategies in ensuring effective integration. The findings imply that multidisciplinary curriculum policies can enhance the relevance and adaptability of Islamic education systems, enabling institutions to respond to modern challenges while maintaining their foundational values.